Pengaruh STEM-PBL Berbantuan Tangram terhadap Kemampuan Berpikir Kreatif Siswa Kelas IV SD - Cahyani, Fitri; Fitri Sriardani, Syafa; Hastuti, Intan Dwi; Lestari, Wahyu (Media Pendidikan Matematika, 2026)
Creative thinking is one of the essential skills that should be developed in mathematics learning, particularly in geometry learning at the elementary school level. However, teacher-centered learning often limits students’ opportunities to explore various alternative solutions to mathematical problems. This study aimed to analyze the improvement of fourth-grade students’ creative thinking skills through the implementation of a STEM-based Problem-Based Learning (PBL) approach assisted by tangram media. This study employed a quantitative approach using a pre-experimental one-group pretest-postest design. The participants consisted of 28 fourth-grade students of SDN 13 Ampenan. Data were collected using a mathematical creative thinking test administered before and after the treatment. Data analysis included descriptive statistics, Shapiro-Wilk normality test, homogeneity test, and paired samples t-test. The results showed that the average score of students’ creative thinking skills increased from 76.43 in the pretest to 86.96 in the postest. The paired samples t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between students’ creative thinking skills before and after the treatment. These findings indicate that the STEM-based Problem-Based Learning approach assisted by tangram media can improve students’ creative thinking skills in geometry learning. Therefore, this approach may serve as an innovative alternative for fostering creative thinking skills among elementary school students.